The Influence of Malt Extraction Adding to UF Fresh Low Fat Cheese on Its Textural Properties - Zahra Shafiei; Mohammad Hojjatoleslamy; Sahel Soha; Mohammad Ali Shariati (Chemical Engineering Diponegoro University, 2014)
Today , demands for reduced fat products such as reduced fat cheeses is growing as it has shown in other food products , however high nutritional value of milk fat as a functional food can’t be ignored. This study deals with investigation of adding malt extract ( in 4 different concentration 0.075 , 0.1 , 0.15 and 0.2 % ) to ultra filtered cheese and comparing them with 2 control including a sample produced of milk containing 3.5 % fat and a 0.93 % fat and their rheological and textural properties evaluated at 3 , 20 , 40 and 60 days. Results indicate reduction of texture properties revealed. Rheological analysis exhibited the texture improvement by adding malt extraction; therefore this product can be use an additive to ultra filtered cheese to enhance its texture.[How to cite this article: Shafiei, Z., Hojjatoleslami, M., Soha, S., and Shariati, M.A. 2014. The Influence of Malt Extraction Adding to UF Fresh Low Fat Cheese on Its Textural Properties. International Journal of Science and Engineering, 6(1):57-60. Doi: 10.12777/ijse.6.1.57-60